2013
DOI: 10.1111/bjd.12461
|View full text |Cite
|
Sign up to set email alerts
|

The safety profile of ustekinumab in the treatment of patients with psoriasis and concurrent hepatitis B or C

Abstract: Antiviral prophylaxis appears to minimize the risk of viral reactivation in patients with concurrent psoriasis and HBV infection. Without effective anti-viral prophylaxis, the risk/benefit of ustekinumab treatment should be carefully assessed in patients with psoriasis and HBV or HCV infection and/or HCC. Close monitoring for HBV and HCV viral load is recommended, particularly for patients with high-risk factors. Serum aminotransferase determination may not be useful for early detection of viral reactivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
81
1
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(98 citation statements)
references
References 62 publications
(192 reference statements)
4
81
1
7
Order By: Relevance
“…A more recent review by Snast et al (17) included 40 patients with psoriasis with chronic HBV infection and found that virus reactivation was documented in 8 (20%) patients on biologic therapy. Our previous study showed that 2 of 7 (29%) patients, not receiving antiviral prophylaxis, exhibited HBV reactivation during treatment with IL-12/23 p40 monoclonal antibody ustekinumab (6). In the present study, the HBV reactivation rate in patients with psoriasis who were positive for HBsAg and did not receive antiviral prophylaxis was 24%, which was lower than that observed in previous studies.…”
Section: Discussioncontrasting
confidence: 79%
See 3 more Smart Citations
“…A more recent review by Snast et al (17) included 40 patients with psoriasis with chronic HBV infection and found that virus reactivation was documented in 8 (20%) patients on biologic therapy. Our previous study showed that 2 of 7 (29%) patients, not receiving antiviral prophylaxis, exhibited HBV reactivation during treatment with IL-12/23 p40 monoclonal antibody ustekinumab (6). In the present study, the HBV reactivation rate in patients with psoriasis who were positive for HBsAg and did not receive antiviral prophylaxis was 24%, which was lower than that observed in previous studies.…”
Section: Discussioncontrasting
confidence: 79%
“…Hsien-Yi CHIU [1][2][3][4] , Rosaline Chung-yee HUI [5][6][7] , Yu-Huei HUANG [5][6][7] , Ruey-Yun HUANG …”
Section: Safety Profile Of Secukinumab In Treatment Of Patients With mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, they met the inclusion criteria [Psoriasis Area Severity Index (PASI) > 18, BSA > 10 with substantial quality of life impairment -DLQ ≥ 10]. Despite a high safety profile well documented in the literature, the application of the biological drug should be preceded by numerous laboratory tests that are intended to exclude foci of infection [1,2].…”
Section: Introductionmentioning
confidence: 99%